Health situation and health care of women aged 50 years and older in rural regions in Germany. (13th November 2019) - Prütz, F; Krause, L; Nowossadeck, E; Thißen, M; Dini, L
Abstract: Background: In many countries demographic changes and regional differences lead to inequalities in healthcare provision. In Germany, this applies especially to rural regions and could affect the healthcare situation of middle-aged and older women in particular. Our study, which is part of the project "Frauen 5.0", explores the health and healthcare situation of women 50 years and older in Northeastern Germany, with focus on outpatient gynaecological and general medical care and reasons for healthcare utilisation. Methods: Our analyses comprise the health situation of women aged 50 years and older, their utilisation of outpatient gynaecologists and general practitioners (GPs), reasons for utilisation, access barriers to outpatient care, the demographic situation and the spatial distribution of gynaecological and GP practices in Northeastern Germany. We use a variety of data sources; main data source is the German Health Interview and Examination Survey for Adults (DEGS1, 2008-2011), which was carried out by the Robert Koch Institute and is representative of the German adult population. Results: There is an unequal distribution of gynaecologic and GP practices in Northeastern Germany, with the highest density in and around Berlin. About 30% of gynaecologists and GPs in the study region are aged 60 years and older. Whereas in all age groups at least 80% of women used GP services in the last 12 months, the use of gynaecologic services declines from 80% in 18- to 29 year-old to 45% in 70- to 79 year-old women. Most important reasons for seeking gynaecological treatment are menopause and early detection of cancer. Conclusions: The analyses show that there is need to ensure adequate health care for women aged 50 and over in rural regions in Germany. Based on the results, within the project "Frauen 5.0" innovative solutions for this task, e.g. interprofessional cooperation, will be identified. Key messages: Analyses of outpatient healthcare services show an unequal distribution of gynaecologic and GP practices in Northeastern Germany; about 30% of the gynaecologists and GPs are aged 60 years and older. Whereas in all age groups at least 80% of women used GP services in the last 12 months, the use of gynaecologic services declines from 80% in 18- to 29 year-old to 45% in 70- to 79 year-old women.